Summary from Doctoral Dissertation Entitled: Th e Ancient Germania and Germans in Polish Historiography. From Naruszewicz to the Present Day - Ciesielski, Mariusz (Studia Europaea Gnesnensia, 2011)
Autoreferat z rozprawy doktorskiej pt. Starożytna Germania i Germanie w historiografii polskiej. Od Naruszewicza po czasy współczesne